A direct test of Auger cascade induced nucleation from heavy element contamination in C3F8 bubble chambers. (1st March 2022) - Bressler, M.; Lamb, N.; Neilson, R.; Windle, S.
Abstract: Understanding and quantifying the gamma-induced bubble nucleation background in clean nuclear recoil detection bubble chambers is of utmost importance to bubble chamber based dark matter searches. We present data confirming the hypothesis that large Auger cascades from high-Z elements such as iodine and xenon dramatically increase the response of C3 F8 bubble chambers to gamma rays. These tests, performed with a small calibration bubble chamber filled with C3 F8 +𝒪(10) ppm xenon, show that the probability of bubble nucleation scales with the rate of xenon inner-shell vacancies, reaching values >10% per K-Shell vacancy for Seitz thresholds of interest to future dark matter searches in bubble chambers. We also place an upper limit on bubble nucleation probability for argon Auger events, relevant to large future bubble chambers which may contain some residual atmospheric argon after the active fluid fill.